Drawing lessons from PISA: Qatar’s use of PISA results - Nouf Abdullah AlKaabi (14147913) (2022)
Worldwide, the Programme for International Student Assessment (PISA) has emerged as a valid and reliable benchmark for assessing students’ performance and for gaining significant influence over educational policy and decision-making. Since 2001, Qatar has engaged in massive educational reform, with high expectations for improving students’ achievement. Although significant growth has occurred in Qatar’s education system, students’ performance in PISA is still lagging. The purpose of this article is to examine PISA against the backdrop of Qatar’s education system. It addresses PISA’s objectives and limitations and identifies two common factors in high-achieving countries, teachers, and assessment. These factors are analyzed to determine how Qatar is developing in these areas, compared with other nations, raising issues that should be considered when using PISA to create policy. Finally, several recommendations are offered for policy makers. Other Information Published in: PROSPECTS License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11125-022-09619-4